Comparative study of the in vitro fermentative characteristics of fenugreek gum, white bread and bread with fenugreek gum using human faecal microbes. Issue 2 (April 2015) - Roberts, K.T.; Allen-Vercoe, E.; Williams, S.A.; Graham, T.; Cui, S.W.
Abstract: The accumulation of short chain fatty acids (SCFA) from the fermentation of three substrates, extruded fenugreek gum, bread with 10% extruded gum and control bread, based on faecal microbiota from three donors was evaluated. Faecal samples were not pooled so each substrate was evaluated for SCFA production with each individual donor׳s faecal sample. SCFA profiles varied with substrates and donors, with fenugreek gum having the highest accumulation of SCFA after 12 h. Donors were a Caucasian Canadian, a black Jamaican and a black Trinidadian, the latter of whom was culturally exposed to fenugreek. This Trinidadian׳s SCFA profiles were consistently higher for fenugreek gum than the other donors. This study evaluated fenugreek gum both as a functional food and nutraceutical. Extruded Fenugreek gum in a bread gave different SCFA profiles than the extruded fibre alone despite the same quantity of fenugreek gum being used. Graphical abstract: Butyric, propionic, acetic acid and total SCFA accumulation for fenugreek gum. Highlights: SCFA profile varied with food substrates and donor faecal microbial composition. Fermentation profile for fenugreek as a functional food and nutraceutical differed. Fenugreek gum accumulated more SCFA than control bread and bread with fenugreek gum. This study found SCFA may be influenced by microbial adaptation to cultural diet.